2017
DOI: 10.1097/md.0000000000007854
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum adipokine levels and radiographic progression in patients with ankylosing spondylitis

Abstract: The immunomodulatory effects of adipokines have been extensively studied in rheumatic diseases, and there is a paucity of information regarding their effects on bone metabolism.The aim of this study was to investigate the relationships between serum adipokines levels and radiographic progression over 2 years in patients with ankylosing spondylitis (AS).In this preliminary longitudinal study, we prospectively recruited 20 consecutive male patients with AS and 11 gender- and age-matched healthy subjects. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…38 Furthermore, and as suggested above, it is likely that adiponectin is strongly associated with early radiographic disease 45 and radiographic progression in RA, 26 irrespective of the metabolic status of the patient. 38,45 In AS, adiponectin serum levels seem to be comparable between patients and healthy individuals 4042 and do not correlate with disease activity. It has been suggested that high-molecular-weight adiponectin might offer protection from radiographic progression in these patients.…”
Section: Inflammatory Pathways In Obesity and Rheumatic Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…38 Furthermore, and as suggested above, it is likely that adiponectin is strongly associated with early radiographic disease 45 and radiographic progression in RA, 26 irrespective of the metabolic status of the patient. 38,45 In AS, adiponectin serum levels seem to be comparable between patients and healthy individuals 4042 and do not correlate with disease activity. It has been suggested that high-molecular-weight adiponectin might offer protection from radiographic progression in these patients.…”
Section: Inflammatory Pathways In Obesity and Rheumatic Diseasesmentioning
confidence: 98%
“…Although not supported by all studies, 32 resistin seems to be increased in serum from AS patients and associated with radiological progression of the disease. 40,41,50 It is rather unclear if there is any correlation between its levels and disease activity. A study in PsA patients suggested that resistin is also increased in these patients.…”
Section: Inflammatory Pathways In Obesity and Rheumatic Diseasesmentioning
confidence: 99%
“…The first stage is the inflammation driven mainly by TNFα, which causes erosions in cartilage and bone; these lesions are then filled in by fibrous tissue, which is later ossified in the last stage leading to abnormal bone outgrowth. New bone formation is actually a hallmark of the disease and is represented by syndesmophytes, bone bridges between the vertebral bodies and subsequent complete ankylosis of the spine [51,86]. Undoubtedly, these productive bone lesions typical of AS deeply impact quality of life in the long-term, since they irreversibly constrain mobility of the spine [87].…”
Section: Adipokines and Spamentioning
confidence: 99%
“…In parallel, the question of the potential influence of adipokines on the progression of spinal ossifications has consistently been examined. Certain studies reported that serum leptin was more elevated in patients with syndesmophytes compared to patients without ( 72 , 73 ) and one study reported the association between the changes in serum leptin at 2 years and radiographic progression ( 74 ). In parallel, visfatin but not resistin or adiponectin have been linked to worsening of the radiographic spinal ossification score (modified stoke ankylosing spondylitis spinal score [mSASSS]) ( 75 ).…”
Section: Adipokines In Rheumatoid Arthritismentioning
confidence: 99%